2015
DOI: 10.1016/j.crci.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

An efficient protocol for the one-pot multicomponent synthesis of polysubstituted pyridines by using a biopolymer-based magnetic nanocomposite

Abstract: A biopolymer cellulose-based magnetic composite nanocatalyst was prepared and characterized by using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). Then, it was used efficiently in the multicomponent synthesis of polysubstituted pyridines under mild reaction conditions and using an easy work-up procedure at room temperature in ethanol. The nanocatalyst can be recovered easily and reused several times without significant loss of catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Therefore, the development of new procedures for their synthesis is still a desirable goal. Due to the wide range of applications and pharmacological activity of 2-amino-3-cyanopyridine derivatives, a variety of reagents and catalysts such as ytterbium perfluorooctanoate [Yb(PFO) 3 ] (37), Graphene oxide (38), 2,2,2-trifluoroethanol (39), Fe 3 O 4 /cellulose (40), ionic liquids (41), and Au/MgO (42) have been reported for the synthesis of these compounds. However, most of these procedures suffer from one or more drawbacks such as the use of expensive metal catalysts, harsh reaction conditions, tedious multistep syntheses, use of toxic solvent, complicated reaction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of new procedures for their synthesis is still a desirable goal. Due to the wide range of applications and pharmacological activity of 2-amino-3-cyanopyridine derivatives, a variety of reagents and catalysts such as ytterbium perfluorooctanoate [Yb(PFO) 3 ] (37), Graphene oxide (38), 2,2,2-trifluoroethanol (39), Fe 3 O 4 /cellulose (40), ionic liquids (41), and Au/MgO (42) have been reported for the synthesis of these compounds. However, most of these procedures suffer from one or more drawbacks such as the use of expensive metal catalysts, harsh reaction conditions, tedious multistep syntheses, use of toxic solvent, complicated reaction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previously proposed mechanism for the synthesis of products 8 or 9, reaction were proceeded by aerobic auto oxidation of 13 0 to products 8 or 9 (Scheme 5). [23][24][25] In contrast to our expected products 13 0 , we observed that 13 0 was converted to 2-amino-3-cyanopyridines (8 and 9) via a hydride transfer which was named anomeric based oxidation (ABO) as well as Cannizzaro reaction (Scheme S1 †), H 2 releasing from tricyclic orthoamide (Scheme S2 †) and etc. [34][35][36][37][38] For this reason, reaction was performed without any molecular oxygen under nitrogen and argon atmospheres.…”
Section: Catalytic Application Of [Co(tppaso 3 H)]cl In the Synthesis Of Target Moleculesmentioning
confidence: 68%
“…A possible mechanism for the synthesis of 8 or 9 is described in Scheme 5. [23][24][25] Firstly, [Co(TPPASO 3 H)]Cl activates the aldehyde 1 and malononitrile 2 to provide intermediate 1 0 and 2 0 , respectively. The Knoevenagel condensation between 1 0 and 2 0 was happened to produce the arylidenemalononitrile 10.…”
Section: Catalytic Application Of [Co(tppaso 3 H)]cl In the Synthesis Of Target Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…condensation between the aromatic aldehyde and dimedone; the resulting α,βunsaturated ketone reacts with the 2-aminobenzimidazole or its corresponding thioderivative via a Michael addition, giving an acyclic compound which undergoes a further intramolecular cyclization. Similar catalysts were also applied for the synthesis of 2-amino-4H-chromenes [107] and highly substituted pyridines [84].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%